Design and implementation of wireless power transfer systems - Yu, Xiecun (Nanyang Technological University, 2022)
With the technology rapidly developed today, people’s demand for electric energy is highly increasing. And wireless power transfer, as a technology that can transfer electric power without any physical connection, is attracting more attention and there is more research on it. In this dissertation, design of a wireless power transfer is introduced, in which the coil design is illustrated more. Besides, both a mathematical model and a simulation model is built in the dissertation for the system operation. And in order to achieve output regulating in the system, phase shift modulation is used on the inverter. With the phase shift angle changing, the system output voltage is kept constant, but it has an increasing loss in the switching devices. A power loss model is then developed and used in the simulation to study the relationship between the system power loss and the power loss of devices with different profile. It is found that the inverter loss is higher at light load and the power loss of higher profile devices can be similar to the power loss of lower profile devices. In this case, lower profile devices can be given more priority in device selection.